1997
DOI: 10.1520/jfs14231j
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQA1 and Polymarker Allele Frequencies in Two New York City Jewish Populations

Abstract: Allele and genotype frequencies were determined for the HLA-DQA1 and Amplitype® Polymarker loci (low density lipoprotein receptor (LDLR), glycophorin A (GYPA), hemoglobin G gammaglobin (HBGG), D7S8, and group-specific component (Gc)) in Hasidic and non-Hasidic Ashkenazi New York City Jewish subpopulations. For all loci tested, except HBGG, the 2 subpopulations meet the assumption of Hardy-Weinberg equilibrium. Comparison of various allele and genotype frequencies for the Hasidic and the non-Hasidic groups show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…We found that the Hasidic and non-Hasidic populations did not differ from each other at these loci, but the Hasidic population did differ from a reference Caucasian population at 2 loci, HLA-DQA1 and D7S8 [2].…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…We found that the Hasidic and non-Hasidic populations did not differ from each other at these loci, but the Hasidic population did differ from a reference Caucasian population at 2 loci, HLA-DQA1 and D7S8 [2].…”
Section: Introductionmentioning
confidence: 55%
“…Genomic DNA was extracted [2] from peripheral blood samples of volunteers from the Hasidic and non-Hasidic Jewish populations of New York City. All samples were collected with informed consent that they may be used anonymously for other research purposes.…”
Section: Samplesmentioning
confidence: 99%
See 3 more Smart Citations